THE FIRST RECORD OF THE ORECTOLOBIFORM SHARK GENUS CEDERSTROEMIA (ELASMOBRANCHII, ORECTOLOBIDAE) IN ASIA (KASHIMA FORMATION, UPPER CRETACEOUS; OYUBARI AREA, HOKKAIDO, JAPAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
We described fossil teeth assigned to the orectolobiform shark genus, Cederstroemia collected from the tuffaceous sandstone of the Kashima Formation (Santonian) in the Oyubari area, Hokkaido, Japan. This is the first report of fossil remains of Cederstroemia from Asia. Due to the small number of specimens and their poor preservation, we left the studied material in open nomenclature as Cederstroemia sp. At the same time, the studied material may belong to a new previously undescribed morphology of Cederstroemia. The occurrence of Cederstroemia fossils in Japan indicates that this genus dispersed to the northwestern part of the Pacific Ocean in the Late Cretaceous, which considerably extends the range and previously known habitat of this genus.